posted by Kayla on .
If you are to solve the equation for x, first try to get the variable on one side of the equation.
Let's subtract 2x from both sides to start (whatever operation you do to one side of an equation you must do to the other side as well):
6 - x - 2x = 2x - 2x + 9
6 - 3x = 9
Now let's subtract 6 from both sides:
6 - 6 - 3x = 9 - 6
-3x = 3
Divide both sides by -3 to get x by itself and solve the equation:
-3x/-3 = 3/-3
x = -1
Does this check with the original equation? Substitute -1 for x and see if it checks out. It always helps to check your work!
I hope this will help.
THANK YOU SO MUCH! that helps me alot!